Effects of a novel method of anesthesia combining propofol and volatile anesthesia on the incidence of postoperative nausea and vomiting in patients undergoing laparoscopic gynecological surgery - Kawano,Hiroaki (2016)
BACKGROUND: We investigated the effects of a novel method of anesthesia combining propofol and volatile anesthesia on the incidence of postoperative nausea and vomiting in patients undergoing laparoscopic gynecological surgery. METHODS: Patients were randomly divided into three groups: those maintained with sevoflurane (Group S, n = 42), propofol (Group P, n = 42), or combined propofol and sevoflurane (Group PS, n = 42). We assessed complete response (no postoperative nausea and vomiting and no rescue antiemetic use), incidence of nausea and vomiting, nausea severity score, vomiting frequency, rescue antiemetic use, and postoperative pain at 2 and 24 h after surgery. RESULTS: The number of patients who exhibited a complete response was greater in Groups P and PS than in Group S at 0-2 h (74%, 76% and 43%, respectively, p = 0.001) and 0-24 h (71%, 76% and 38%, respectively, p < 0.0005). The incidence of nausea at 0-2 h (Group S = 57%, Group P = 26% and Group PS = 21%, p = 0.001) and 0-24 h (Group S = 62%, Group P = 29% and Group PS = 21%, p < 0.0005) was also significantly different among groups. However, there were no significant differences among groups in the incidence or frequency of vomiting or rescue antiemetic use at 0-24 h. CONCLUSION: Combined propofol and volatile anesthesia during laparoscopic gynecological surgery effectively decreases the incidence of postoperative nausea. We term this novel method of anesthesia "combined intravenous-volatile anesthesia (CIVA)".